Skin-Attachable, Stretchable Electrochemical Sweat Sensor for Glucose and pH Detection - Oh, Seung Yun; Hong, Soo Yeong; Jeong, Yu Ra; Yun, Junyeong; Park, Heun; Jin, Sang Woo; Lee, Geumbee; Oh, Ju Hyun; Lee, Hanchan; Lee, Sang-Soo; Ha, Jeong Sook (American Chemical Society, 2018)
As part of increased efforts to develop wearable healthcare devices for monitoring and managing physiological and metabolic information, stretchable electrochemical sweat sensors have been investigated. In this study, we report on the fabrication of a stretchable and skin-attachable electrochemical sensor for detecting glucose and pH in sweat. A patterned stretchable electrode was fabricated via layer-by-layer deposition of carbon nanotubes (CNTs) on top of patterned Au nanosheets (AuNS) prepared by filtration onto stretchable substrate. For the detection of glucose and pH, CoWO4/CNT and polyaniline/CNT nanocomposites were coated onto the CNT-AuNS electrodes, respectively. A reference electrode was prepared via chlorination of silver nanowires. Encapsulation of the stretchable sensor with sticky silbione led to a skin-attachable sweat sensor. Our sensor showed high performance with sensitivities of 10.89 mu A M-1 cm(-2) and 71.44 mV pH(-1) for glucose and pH, respectively, with mechanical stability up to 30% stretching and air stability for 10 days. The sensor also showed good adhesion even to wet skin, allowing the detection of glucose and pH in sweat from running while being attached onto the skin. This work suggests the application of our stretchable and skin-attachable electrochemical sensor to health management as a high-performance healthcare wearable device.
Keywords: BLOOD-GLUCOSE; GRAPHENE FOAM; PERFORMANCE; ELECTRODE; SUPERCAPACITORS; FABRICATION; NANOSTRUCTURES; NANOPARTICLES; TRANSPARENT; NANOFIBERS